The Socio-Economic Effects of the COVID-19 National Lockdown on South Africa and its Response to the COVID-19 Pandemic: Array - Chitimira, Howard; Hamadziripi, Friedrich (Acta Universitatis Danubius. Juridica, 2021)
The coronavirus (COVID-19) pandemic has caused a global public health emergency. In the absence of approved and effective prophylactics and therapeutics, almost all countries have resorted to some version of national lockdown coupled with social distancing and enhanced hygiene measures to curb the spread of the pandemic. The COVID-19 has infected almost fifty million people globally, with more than a million deaths so far. Although national lockdowns have been employed as the primary response to the COVID-19 pandemic, they have also resulted in untold economic devastation to South Africa. Millions of people in the informal sector have been impoverished due to the COVID-19-induced lockdown. More people have become unemployed, the Gross Domestic Product (GDP) of almost all the nations have significantly contracted and public debt has rapidly increased while South Africa’s national budget has been severely strained. This article examines the socio-economic effects of the COVID-19-induced lockdown on South Africa and its response to the COVID-19 pandemic. Reference will be made to Tanzania and Sweden which have shunned lockdowns. This is done for comparative purposes and to inform policy reform.